Progression Model Tissue Microarray (TMA) for the Study of Uterine Carcinomas. Issue 5 (30th May 2013) - Arafa, Mohammad; Boniver, Jacques; Delvenne, Philippe
Abstract : Cervical and endometrial uterine carcinomas are heterogeneous groups of cancers, which are preceded by preneoplastic lesions. More accurate tools are needed to improve the diagnosis and to define markers which may be relevant for the diagnosis, prediction of disease progression and therapeutic response. High throughput technologies for testing and validating molecular targets in cancer lesions and in their precursors are presently available. Among them, the tissue microarray (TMA) presents the advantage of a morphological control of the analyzed tissue fragment. In this article, we review the different aspects of the TMA technology with a special consideration to a uterine carcinogenesis model.